Smart Cradle For Baby Using FN-M16P Module - Levy, M; Bhiwapurkar, Deepali; Viswanathan, Gokul; S, Kavyashree; Yadav, Pawan Kumar (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2019)
The paper cites the Infant Monitoring System with Real-Time Alerts to Parents using GSM. Activity Monitoring includes Infant’s cry detection which makes the cradle swing with pre-recorded voice play and alert to parents for their intimidation. This type of cradle is useful for mothers who are highly educated and insisting to go for work and has no time to take care of their infants. Cry detector system which detects the baby cry and swings the cradle until the baby stops crying. The swinging action is due to DC motor. The user can control the speed of the cradle as per his need. FN-M16P module will have recorded voice input of the mother and plays it whenever the baby cries for a long time. The ultrasonic and accelerometer sensors are used for detecting respiratory and non respiratory movements of the baby.